GRAB-AND-GO COFFEE : KETIKA KONSUMEN MENGANGGAP MINUM KOPI TIDAK LAGI HARUS “NONGKRONG” - Novita Novita; Kelvin Liekardo (Value : Jurnal Manajemen dan Akuntansi, 2020)
Third Wave of Coffee is the last era of coffee development (for now), where coffee entrepreneurs began to create a special appreciation for coffee. In this era, consumers began to realize that coffee is not just a commodity to consume, but coffee has become an important part of every consumer's life. This research was conducted to determine changes in experiential marketing in grab-and-go coffee shops. Regular consumers are more influenced by experience quality created by coffee shops, where product quality and service quality are considered less important. Experience quality plays a major role in adding value to the product, further encouraging consumers to re-visit a coffee shop. The analysis technique uses PLS 3.0 with 170 respondents. The results showed that product quality and service quality affect the satisfaction. While experience quality has no effect. Satisfaction has an effect on repurchase intention on grab-and-go coffee. Keywords : product quality, service quality, experience quality, satisfaction, repurchase intention.